Case report: Remarkable response to a novel combination of mitotane, etoposide, paraplatin, and sintilimab in a patient with metastatic adrenocortical carcinoma - Weng, Yan; Wang, Lin; Wang, Xiao-Yi; Fan, Xin-Xiang; Yan, Li; Li, Zhi-Hua; Zhang, Shao-Ling (Frontiers in Endocrinology, 2023)
Background: Adrenocortical carcinoma (ACC) is a rare malignancy with poor prognosis and limited treatment options for metasta ses. However, new effective regimens are emerging for specific conditions in metastatic ACC.We report a case of a 36-year-old male diagnosed with metastatic ACC, who had a large left adrenal mass (158 mm×112 mm), and multiple metastases in the liver and lungs. Genetic testing revealed a microsatellite instability-high (MSI-H) tumor, a splice mutation in MLH1, and a high tumor mutational burden (TMB). After the left adrenalectomy, he received sequential treatment with a combination of mitotane, etoposide, paraplatin (EP-M), and sintilimab. His condition has been assessed as stable disease since the sixth cycles of the combined regimen.This case highlights the remarkable response of our patient's ACC with MSI-H tumor, MLHI spice mutation, and high TMB to treatment with a novel combination of EP-M and sintilimab. Our findings suggest a promising therapeutic option for patients with similar molecular profiles .